GIVING IN AN ISLAMIC PERSPECTIVE - Abd Jalil, Mohamad Isa (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: The purpose of this study is to shed light on the underlying concept of giving in the perspective of Islam. Methodologically, this study employs qualitative systematic data processing approach. The conceptual framework is developed from the Quran, Hadith, and the story of the Prophet and his companions. This study also refers to a conventional theory such as Altruism, Socially Consumer Behaviour, and Social Exchange Theory. Several previous empirical studies were also recorded to support the proposition. This study proposes four variables that might influence people to give, namely, targhîb, tarhîb, ihsân and ikhwah. By realizing many other factors that may influence the giving behaviour, this study only focuses on the Islamic religious perspective. This article also brought opportunities to investigate conceptually and empirically other factors that could affect giving behaviour. To the best of the author’s information, there is only a small number of studies that have been done concerning the influence of religion towards giving behaviour. And it is at his juncture the novelty of this study lies.Keywords: giving, Islamic charity, targhîb, tarhîb, ihsân, ikhwah